Enhanced corrosion resistance of Ni/Sn nano-electrodeposited metal foam for flow field application in simulated PEMFC cathode environment. (1st October 2022) - Wang, Zichen; Xia, Yuzhen; Lei, Hangwei; Hu, Guilin
Abstract: Metal foam, with large specific surface area, suffers serious corrosion problems, as flow field in proton exchange membrane fuel cell (PEMFC). Ni/Sn nanoparticles are deposited onto the surface at galvanostatic and gradient current, respectively. The morphology of coated foams is examined by scanning electron microscopy (SEM), coupled with x-ray diffraction (XRD) and energy dispersive spectroscopy (EDS). The effect of deposited current on its corrosion resistance in simulated PEMFC cathode environment is evaluated by Tafel polarization test, constant potential test and electrochemical impedance spectra. The results show that the coating effectively improved the stability of metal foam in acid environment. A uniform and dense protective film is formed by Ni/Sn electrodeposition at a gradient current density from 0 to 40 mA cm −2 . Its corrosion current at 25, 50 and 80 °C, accounts around 38.0%, 47.3% and 46.7%, respectively, of the value of uncoated metal foam. The most positive corrosion current is obtained, −0.12 mA, which is explained to higher coating resistance (Rcoat ). No obvious pitting is depicted in the surface morphology after 8 h, which further proves its high corrosion resistance. Highlights: Ni/Sn are electrodeposited onto metal foam for PEM fuel cell application. Ni/Sn coated Ni foam performs higher corrosion resistance than uncoated Ni foam. The galvanostatic and gradient current modes result different surface morphologies. A dense and compact Ni/Sn film obtained at gradient current shows better stability.